Guinea : Poverty Reduction Strategy Paper-Progress Report. (IMF Staff Country Reports; Country Report ;, 2015)
This Poverty Reduction Strategy Paper (PRSP) highlights the progress report for Guinea. In order to strengthen the dynamics undertaken in the area of planning and implementing the poverty reduction strategy, with the support of its development partners, the government in September 2012 undertook the process of preparing its third PRSP, which covers 2013-2015. PRSP-3 implementation for the 2013 annual period registered disappointing results, explained by the unfavorable domestic as well as international context (political instability and falling commodities prices) and poor performance in growth sectors such as mining. Investments in infrastructures in support of growth increased substantially. Support and strengthening of the efforts made in this area will make it possible to ensure stable GDP growth rates of approximately 7.8 percent between 2013 and 2015. However, investments in the energy sector have yielded disappointing results as a result of the poor condition of the network, commercial management problems, and other factors.